Fitness profile of young female volleyball players - Pocek, S.; Vukovic, J.; Jaksic, D.; Lakicevic, N.; Messina, G.; Bianco, A.; Drid, P. (Medicina dello Sport, 2020)
BACKGROUND: Factors that influence performance in volleyball, in terms of motor skills, refer to muscle power, speed and agility. This study aimed to examine the abilities and physical characteristics of female volleyball players in terms of age and player specialization. METHODS: A total of 35 subjects (junior and cadet age), participated in this study. Subjects were assessed for body height, mass, spike and block reach, and body composition. Vertical jump, standing broad jump, spike and block jump were tests used to measure leg power. The running speed was evaluated with a 20-m single-sprint effort. The change of direction speed was assessed with a T-test, the sprint 9-3-6-3-9 m forward-backward shuttle and sprint 9-3-6-3-9 m with 180° turns. Two-way ANOVA with LSD post-hoc test was applied in order to examine whether there is a statistically significant difference (P=0.05) between team, position and their interaction, using SPSS v. 20.0. RESULTS: There was not a statistically significant interaction between the effects of team and position on anthropometric measures and motor abilities of volleyball players. Age, training years and technical-tactical knowledge of junior players led to better performance in all conducted tests of motor abilities in comparison to young female cadet players. According to the position, the majority of motor tests showed no differences between players. CONCLUSIONS: These results might be useful for strength and conditioning professionals who work with young female volleyball players of a similar age and competition level.